ENUMERATION OF THE GENUS ATHYRIUM IN JAVA AND BALI - WARDANI, WITA -; ADJIE, BAYU -; YULITA, KUSUMADEWI SRI; LESTARI, WENNI SETYO; SALAMAH, ANDI - (REINWARDTIA, 2024)
We present a list of Athyrium species from Java and Bali based primarily on morphological examination. Some of disputed species were confirmed through molecular assess-ment. There are eight species of Athyrium in Java and two in Bali, none of them are endemic, but distribution of one species outside Java is uncertain. We provide the list with description, key to the species, and notes on taxonomy or distribution.